Agrivoltaic innovation index: A composite scientometric tool for tracking global research readiness - Kabir, Masud; Ekici, Sami (Elsevier B.V., 2026)
Agrivoltaics has rapidly emerged as a key solution within the energy-agriculture nexus, yet existing reviews and bibliometric studies largely focus on publication growth, system typologies, or localized techno-economic performance, without providing a quantitative framework to assess innovation readiness across the global research landscape. To address this gap, this study proposes the Agrivoltaic Innovation Index (AII), a composite scientometric indicator designed to represent the multidimensional structure of innovation in agrivoltaic research beyond publication volume and citation counts. Integrated from seven sub-indices, including conceptual novelty, interdisciplinarity, and technological readiness, AII uses entropy-based weighting to enable comparative assessment of papers, institutions, and countries, respectively. Results indicate that global agrivoltaic innovation is structurally uneven; high publication volume often decouples from high innovation readiness. Notably, several low-output countries achieve high AII values, a pattern that may reflect focused research contributions but should be interpreted with caution, given the sensitivity of low-output-country scores to individual internationally co-authored papers. Robustness tests, including Pearson correlation and machine learning internal consistency checks, provide support for the structural coherence of the AII as a diagnostic framework. By moving beyond descriptive reviews, the AII offers a quantitative perspective to distinguish research maturity and regional innovation pathways. This framework suggests a potentially transferable methodology for benchmarking sustainability-oriented research, supporting evidence-based planning and policy prioritization in the energy-agriculture nexus. © 2026 The Author(s).